Membangun Literasi Reflektif bagi Komunitas Penulis di Sekolah Jawa Timur melalui Kegiatan Bedah Buku dan Workshop Puisi Bertema Kartini - Dwi Nur Cahyani Sri Kusumaningtyas; Zulidya Rusnalasari; Pratiwi Retnaningdyah; Ayu Saraswati; Suyanti Umayfa; Audrey Titaley; Revalina Fauzia; Brillyan Pakerti (ABISATYA : Journal of Community Engagement, 2025)
The community service program entitled Building Reflective Literacy for the Writer Community in East Java Schools through Book Review Activities and Kartini-Themed Poetry Workshops aims to improve reflective literacy and creative expression skills among educators and literacy practitioners. This program is motivated by the limited space for teachers and the writing community in schools to develop reflective literacy practices that integrate cultural values and gender awareness. The main purpose of this activity is to strengthen participants' understanding of Kartini's emancipation spirit through literary exploration, especially by associating historical reflection with the context of today's education. The implementation of the program includes two main activities: a book review of Kartini's Trilogy which presents authors and academic speakers, and a workshop on writing reflective poems inspired by Kartini's values of struggle. The methods used include participatory dialogue, collaborative learning, and creative writing practices, which allow participants to interact critically with the text while expressing personal reflection through literary works. The results of the activity showed an increase in participants' awareness of gender equality issues, literary appreciation, and creative writing skills. In addition, this activity encourages collaboration between schools, teachers, students, and literacy communities in East Java, forming a sustainable network for future literacy development. The novelty of this program lies in the integration of cultural heritage, reflective pedagogy, and creative expression as a means of community empowerment. Overall, this activity shows that reflective literacy can be an effective forum to strengthen the value of education, cultural understanding, and social cohesion within the framework of sustainable community development.